Evaluation of the cytotoxicity, genotoxicity, mutagenicity, and antimutagenicity of propolis from Tucuman, Argentina - Nieva Moreno, María Inés (2005)
This study evaluates the toxic, genotoxic/mutagenic, and antimutagenic effects of propolis extract from Amaicha del Valle, Tucumán, Argentina. The cytotoxicity assays carried out with the lethality test of Artemia salina revealed that the LD50 was around 100 μg/mL. Propolis extracts showed no toxicity to Salmonella typhimurium TA98 and TA100 strains and Allium cepa at concentrations that have antibiotic and antioxidant activities. Otherwise, for the testing doses, neither genotoxicity nor mutagenicity was found in any sample. The propolis extracts were able to inhibit the mutagenesis of isoquinoline (IQ) and 4-nitro o-phenylenediamine (NPD) with ID50 values of 40 and 20 μg/plate, respectively. From this result, the studied propolis may be inferred to contain some chemical compounds capable of inhibiting the mutagenicity of direct-acting and indirect-acting mutagens. A compound isolated from Amaicha del Valle propolis, 2′,4′- dihydroxychalcone, showed cytotoxic activity (LC50 values of 0.5 μg/mL) but was not genotoxic or mutagenic. Furthermore, this compound was able to inhibit the mutagenicity of IQ (ID50 values of 1 μg/plate) but was unable to inhibit the mutagenicity of NPD. Our results suggest a potential anticarcinogenic activity of Amaicha del Valle propolis and the chalcone isolated from it. © 2005 American Chemical Society.